Coporate Social Responsibility (CSR) dan Struktur Kepemilikan (Kepemilikan Institusional, Kepemilikan Manajerial, Kepemilikan Asing) Terhadap Nilai Perusahaan - Elin Erlina Sasanti; Animah Animah; M Ali Fikri (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
This research aims to examine the influence of Corporate Social Responsibility (CSR) and ownership structure (institutional ownership, managerial ownership, foreign ownership) on company value in basic industrial and chemical manufacturing companies listed on the Indonesian Stock Exchange for the 2019-2021 period. The Grand Theory used in this research is legitimacy theory and stakeholder theory. The type of research used in this research is quantitative research. The data source obtained for this research is a secondary data source obtained from www.idx.co.id. The research population is basic industrial and chemical companies that went public in 2019-2021. The sampling technique was purposive sampling with the criteria: basic industrial and chemical companies that went public, companies that had no losses and were listed from 2019-2021 with a sample size of 63. The test tool used was multiple regression using the SPSS test tool. The research results show that Corporate Social Responsibility (CSR) has a negative effect on company value. Meanwhile, institutional ownership, managerial ownership and foreign ownership have no effect on company value. This explains that the implementation of CSR is only to fulfill the social contract of the company and society because if the greater the funds spent on this activity, the company's profitability will decrease so that the value of the company also decreases. Meanwhile, the ownership structure cannot intervene to increase company value during the pandemic because external factors have a stronger influence.